Surface modification of recycled polymers in comparison to virgin polymers using Ar/O2 plasma etching. Issue 12 (2nd August 2022) - Amberg, Martin; Höhener, Marion; Rupper, Patrick; Hanselmann, Barbara; Hufenus, Rudolf; Lehner, Sandro; Perret, Edith; Hegemann, Dirk
Abstract: Low‐pressure plasma etching of a recycled polyethylene terephthalate (PET) film is studied in comparison to virgin PET and polypropylene (PP) using a capacitively coupled radio frequency (RF) plasma reactor. Recycled polymers are distinguished by increased impurity content and weakened mechanical properties, both affecting plasma etching and adhesion processes. Mild plasma conditions have been selected to maintain the material bulk properties of the polymers. The etch rates and the morphology of the polymer samples were thus determined at floating potential compared with etching at the RF electrode for varying argon/oxygen gas mixtures, etching duration, and sample size. Thermoanalytical and X‐ray techniques were used to characterize the polymer before and after the plasma etching treatment. Finally, adhesive‐tape peel tests proved that excellent adhesion of silver coatings can also be achieved on a plasma‐treated recycled PET film. Abstract : Recycled and virgin polymers are studied by mild Ar/O2 plasma etching. Low ion energy reduces the etch rate but also the heat transfer to the substrate to remain below the glass transition temperature of the polymer preserving its bulk properties. Regardless of structural differences of the recycled polymer compared with the virgin, adjusted plasma etching enables similar adhesion of silver films opening up new opportunities in the reuse of polymer materials.